Madame Chair A Political Autobiography of an Unintentional Pioneer - Westwood, Richard (University Press of Colorado, 2007)
Jean Westwood called herself an unintentional pioneer. Although she worked hard to achieve what she did, she did not actively seek or expect to reach what was arguably the most powerful political position any American woman had ever held, chair of the national Democratic Party. A Utah national committeewoman and member of the reform committee that reorganized the party, Westwood answered George McGovern's call to lead his presidential campaign. In the dramatic year of 1972, she became "chairman" of the party, McGovern lost in a landslide, Nixon was reelected, and a covert operation burglarized Democratic National Committee headquarters at the Watergate. Westwood provides an inside account of a period that reshaped national politics. Second-wave feminism-"women's liberation"-and the civil rights and antiwar movements opened the way. As a major player in political reform, Jean Westwood both helped build that road and traveled it.